Tabsīṭ Kitāb Matn al-Ājurrūmiyyah li-taʿlīm ʿilm al-naḥw li-al-ṭullāb al-mubtadiʾīn bi-Maʿhad al-Muhājirīn al-Thālith Purwakarta - Firdaus, Farhan (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
Syntax books in Indonesia are generally written by syntax experts from the middle east so that the selection of material and their arrangement as well as the way of presentation are only suitable for Arabic students. The Jurumiyyah book became a textbook in the teaching of syntax for the novice students at the Al-Muhajirin 3 Purwakarta Islamic Boarding School and they had difficulty to comprehend the book very well. Therefore, the researcher tried to simplify the book of Jurumiyyah and hopes that there will be special easier textbooks to learn for novice students in Indonesia. The method used in this research is a descriptive analysis method. The conclusion of this research is that the simplification of the Jurumiyyah book is carried out in three steps, first by reformulation of the chapters which starting from the chapter Kalimat wa Aqsamuhu, Fa’il, Maf’ulu Bih, Naib al-Fa’il, Mubtada and Khabar, Kana and Akhwatuha, Inna and Akhwatuha, Na’tu, ‘Athfu, Taukid, Badal, Hal, Tamyiz, Istitsna, and Idhofat, the second by updating the definitions of several themes with new definitions and the third by removing chapters that are not suitable for the novice students at the al-Muhajirin 3 Purwakarta Islamic Boarding School